Selection of insulation materials with PSI-CRITIC based CoCoSo method - Uluta, Alptekin; Balo, Figen; Sua, Lutfu; Karabasevic, Darjan; Stanujkic, Dragisa; Popovic, Gabrijela (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2021)
The performance effect of construction on energy conservation substantially depends upon application of correct materials and energy saving methodologies. A sizable financial impact is accomplished through insulated walls. The criteria explaining the present wall insulating material options may have different values. Furthermore, they may alter in different aspects, i.e. higher values of certain criteria show a preferable status, while for others they denote an inferior status. In this framework, a variant of compromise is needed, which can be situated through multi-criteria assessment methodologies. To diminish the effect of different methodologies on computational results, few diverse techniques can be considered, with descriptions of the mean predicted values. Thus, drawbacks of certain multi-criteria assessment techniques could be compensated through others. A hybrid methodology through the combination of individual techniques will be accurate if there is a relationship between the values determined through diverse methodologies. In this study, the most efficient insulation material used at external walls is selected by using PSI-CRITIC based CoCoSo Method. The analytical results are important both from financial and engineering point of views as the applied methodology is commercially viable and practically implementable. Precise and up-to-date material properties are derived from the leading companies in the sector.
Keywords: PSI; CRITIC; CoCoSo; insulation materials; building; construction material